1992
DOI: 10.4315/0362-028x-55.12.1009
|View full text |Cite
|
Sign up to set email alerts
|

Listeria in Seafoods: A Review

Abstract: Listeria is an environmental contaminant which has been isolated from marine and fresh waters, as well as various seafoods. Furthermore, Listeria, including Listeria monocytogenes, has been isolated from processed seafood products such as smoked fish, cooked and frozen seafoods, marinated fish, surimi products, etc. The pathogen, L. monocytogenes, does have a certain degree of heat resistance. It was found to survive in internally infected shrimp after boiled for up to 5 min. However, the commercial pasteuriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…Neither the number of pp. were found residents in a house (1)(2)(3)(4)(5)(6)(7)(8)(9), nor the time of sampling rikingly, there (morning or afternoon) influenced the contamination ne species was rate of the sampling sites (data not shown). levels for L.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Neither the number of pp. were found residents in a house (1)(2)(3)(4)(5)(6)(7)(8)(9), nor the time of sampling rikingly, there (morning or afternoon) influenced the contamination ne species was rate of the sampling sites (data not shown). levels for L.…”
Section: Resultsmentioning
confidence: 98%
“…monocytogenes has been isolated from an extensive range of raw and processed food products including pate and other cooked meat products [4], soft cheeses [5], (smoked) fish products [6,7] and vegetables [8]. When this pathogen is isolated from processed foods, it is usually not the result of inadequate heat processing, but rather post-process contamination of the product.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of L. rnonocytogenes in various foods has been shown in many studies to vary considerably [3,6,14,[16][17][18][19][20], making comparisons difficult.…”
mentioning
confidence: 99%
“…Nevertheless, chicken, meats, dairy products and seafood have sometimes been found to have a higher prevalence of the organism than other foods [3,14,16,21,22].…”
mentioning
confidence: 99%
“…are very common. Listeria spp., including L. monocytogenes, have been isolated from processed seafood products such as cooked and frozen seafood, marinated fish, surimi products, and smoked fish (12)(13)(14). A sampling survey on ready-to-eat fish products at both the wholesale and retail level indicated that shrimp and smoked salmon are often contaminated with L. monocytogenes (14).…”
Section: Introductionmentioning
confidence: 99%